Assessing the adverse effects of food coloring additives, particularly in (dairy and meat products) - Noori, Mohammad Asif (Journal of Natural Sciences – Kabul University, 2024)
Color pigments in food are unstable and it changed throughout processing. To preserve this crucial organoleptic trait, different colors are added in food all around the world. Colors, especially artificial colors have adverse effects for all consumers particularly children. This study was conducted in a review-based format, and its aim is to familiarize with the application, source of production, permissible limit, and awareness of the adverse effects of their colors. The use of colors in meat and food products has its own special advantages and disadvantages, because on the one way it solves the relevant technological problems, and on the other way, using them can cover up deliberate changes in the composition of the product and the use of poor quality raw materials. The findings of the present research include understanding the side effects of colors and their use in different products.